Method for efficiently degrading PFAS by using Z-type heterojunction photocatalytic material BN / BiOI
By using the Z-type heterojunction photocatalytic material BN/BiOI, the problem of difficulty in degrading PFAS in the prior art is solved, and an efficient and low-cost PFAS degradation effect is achieved.
Patent Information
- Application Number
- CN202411441405.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to efficiently degrade persistent and stable perfluoro and polyfluoro compounds (PFAS), which are difficult to degrade in the environment, and the effects of existing photocatalytic materials are limited.
Using Z-type heterojunction photocatalytic material BN/BiOI, a composite material of nanotube-shaped BN and nanosphere Bi(NO3)3·5H2O is prepared to form a stable heterojunction, and the photocatalytic characteristics are used to promote the degradation of PFAS.
It realizes low-cost and high-efficiency PFAS degradation, expands the photo response range, improves catalytic activity, and has significant degradation effect. It is suitable for the degradation of various PFASs.
Smart Images

Figure CN119406437A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field, and in particular to a method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI. Background Art
[0002] PFAS (Per and Polyfluoroalkyl Substances) are synthetic organic compounds whose hydrogen atoms on carbon atoms are replaced by fluorine atoms, making PFAS extremely stable and resistant to degradation. PFAS are widely used in the manufacture of waterproof, oil-proof and anti-fouling products such as food packaging materials, textiles, firefighting foams, cosmetics and personal care products. They are also often used in coatings and lubricants to improve the durability and performance of products.
[0003] However, the persistence and stability of PFAS also mean that once they enter the environment, they are difficult to break down. They can enter the human body through various pathways, such as drinking water, food, and air. Long-term exposure to PFAS may lead to a range of health problems, including damage to the immune system, endocrine system, reproductive system, and nervous system.
[0004] In order to deal with the environmental problems caused by PFAS, existing technologies have taken a series of measures to limit the production and use of PFAS. For example, the use of PFAS in specific products, such as food packaging materials and textiles, is prohibited or restricted. In addition, the monitoring and detection of PFAS are being strengthened to understand its distribution and concentration in the environment, and a variety of methods are used to degrade it, but its degradation is difficult. In the current degradation technology, photocatalytic materials are used to promote degradation. For example, SiC / GQDs nanocomposites, Ga / TNTs@AC, Me / TNTs@AC, TiO2 / UV heterojunctions, etc. have limited effects in photocatalytic degradation of perfluorooctane sulfonic acid PFOS. Therefore, an efficient catalytic material is needed to complete the degradation of PFAS. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI.
[0006] A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI, comprising:
[0007] S1. preparing BN / BiOI material;
[0008] S1-1, preparing solution A: dissolving 2-4 mmol Bi(NO3)3·5H2O and 1.5-6.0 mmol BN in 10-30 mL ethylene glycol, stirring for 25-35 min to form solution A; wherein the structure of the BN is a nanotube structure, and the structure of the Bi(NO3)3·5H2O is a nanosphere structure;
[0009] S1-2, preparing solution B: adding 2-4 mmol of KI to 10-30 mL of ethylene glycol, and mechanically stirring for 5-15 min at a mechanical stirring speed of 200-230 rpm to form solution B;
[0010] S1-3, adding solution A dropwise to solution B, stirring for 55-65 min, vacuum drying at 155-165° C. for 10-14 h, and then cooling to 20-25° C. to obtain a solid, and then washing the solid with distilled water and anhydrous ethanol in sequence, and then drying to obtain a BN / BiOI material;
[0011] S2. Degrade PFAS in water;
[0012] The pH of the water to be degraded is adjusted to 2-4, and the BN / BiOI material is added to the water to be degraded to degrade until the PFAS concentration in the water to be degraded drops below the detection limit.
[0013] In the water to be degraded, the concentration of PFAS is 2-100 mg / L, and the addition ratio of BN / BiOI material to the water to be degraded is 50-100 mg:50 ml.
[0014] Note: The above method can improve the existing solvothermal method to form a stable heterojunction. At the same time, the BN / BiOI material itself has photocatalytic properties, which can promote the oxygen vacancies and e - / h +Separation solves the problem that the wide band gap of BN limits its photocatalytic performance. The above method can solve the complicated operation of hydrophobic treatment for PFAS required by the existing method, and can improve the catalytic activity of BN / BiOI composite materials for PFAS. Specifically, nanotubular BN and nanospherical Bi(NO3)3·5H2O have different surface energies and curvatures, and can form a specific interface structure when composited to minimize the total free energy of the system; in the BN / BiOI heterojunction, when irradiated with light, BiOI absorbs light energy to generate electron-hole pairs, and the electrons migrate to BN, while the holes remain in BiOI. Due to the different positions of the conduction band and valence band of BN and BiOI, this separation of electrons and holes can reduce their recombination probability, thereby improving the utilization rate of photogenerated charges. The Z-type heterojunction can also expand the light response range, allowing the material to utilize more light energy, thereby achieving low-cost and high-efficiency degradation, and the degradation of PFAS is diverse and the conditions are relatively mild.
[0015] Furthermore, in S2, the detection limit of the PFAS concentration is 1 mg / L.
[0016] Furthermore, in S2, after the BN / BiOI material is added to the water to be degraded, it is first mechanically stirred for 2 to 3 minutes at 250 to 280 rpm, and then dark adsorption is carried out under lightless conditions, and stirring is performed during the dark adsorption, and the dark adsorption time is 20 to 55 minutes; after the dark adsorption is completed, photocatalytic degradation is carried out under light conditions, and mechanical stirring is performed during the photocatalytic degradation, and the mechanical stirring speed is 150 to 180 rpm.
[0017] Description: The above-mentioned degradation method can improve the degradation efficiency. Through reasonable stirring and existing lighting settings, it can accelerate the progress of the photocatalytic reaction according to the effect of adding BN / BiOI materials to the water to be degraded, thereby improving the overall catalytic efficiency.
[0018] Furthermore, the dripping speed of adding solution A to solution B is 3 to 6 drops / s.
[0019] Note: The BN / BiOI material obtained within the above range has a better structural state and a better degradation effect. Exceeding this range may result in insufficient structural stability.
[0020] Furthermore, the stirring treatment is to continue stirring for 2 to 3 minutes at a stirring speed of 350 to 500 rpm, then stop stirring, turn on the ultrasonic treatment equipment, treat for 3 to 5 minutes at an ultrasonic frequency of 40 to 45 kHz, and then stir and ultrasonicate for 15 to 20 minutes at the same time.
[0021] Note: The above stirring treatment method can make the solid and liquid fully contact, improve the mixing effect, and at the same time, can accelerate the reaction rate, avoid the occurrence of solid particle agglomeration, and improve the consistency of the product.
[0022] Furthermore, the ultrasonic mode of the ultrasonic processing equipment is a pulse mode, and the pulse mode works for 5 seconds and rests for 5 seconds.
[0023] Note: The above-mentioned pulse mode can effectively reduce the heat accumulation caused by continuous ultrasonic action, thereby avoiding the change of material properties caused by overheating of the reactants. At the same time, the pulse mode can give the mixed material a certain static time after each ultrasonic action, which is conducive to the uniform mixing of the mixed material.
[0024] Furthermore, in said S1, after obtaining the BN / BiOI material, it is subjected to multi-level processing;
[0025] The multi-level processing method is: using the BN / BiOI material obtained in S1 as the core particle, firstly depositing a layer of BN particles on the surface of the BN / BiOI material to obtain a single-layer material, and then depositing a layer of BiOI particles on the surface of the single-layer material to obtain a multi-layer BN / BiOI material;
[0026] The particle size of the BN / BiOI material is 30-115 nm, the particle size of the BN particles in the BN particle layer is 20-50 nm, and the particle size of the BiOI particles is 20-40 nm; in the multi-layer BN / BiOI material, the thickness ratio of the BN / BiOI material, the BN particle layer, and the BiOI particles is 4:1-2:2-3.
[0027] Description: The above-mentioned multi-level treatment can use BN / BiOI material as the core particle, and sequentially deposit BN and BiOI on the BN / BiOI material as the core particle. The unique electronic structure and catalytic activity of BN can promote the catalytic reaction. At the same time, the visible light responsiveness of BiOI can generate photogenerated electrons and holes under light conditions to induce degradation reactions. The design of the above-mentioned shell structure enables the photocatalytic performance of BiOI to be better exerted, because the shell can provide more reaction interfaces and light absorption areas, and the BN shell in the shell structure can confine the reactants so that the reactants react inside the shell, thereby improving the selectivity and efficiency of the reaction.
[0028] Further, depositing a layer of BN particles on the surface of the BN / BiOI material includes:
[0029] 1) Using an active agent at a ratio of 1-5 ml: 10-20 g to surface modify the particles of the BN / BiOI material and dry the particles to obtain a pretreated BN / BiOI material; the surface modification is performed by spraying the particles onto the surface;
[0030] 2) Take a mixture of 1-2% BN in boric acid; add zirconium oxide powder of the same mass as BN into the mixture;
[0031] 3) Add the pretreated BN / BiOI material to the BN boric acid mixture at a ratio of 1g:5-8ml, apply a voltage of 45-50V, and a current density of 10-15mA / cm 2 , and deposit for 25 to 30 minutes to obtain the single-layer material.
[0032] Note: The above method first pre-treats the surface of the BN / BiOI material to improve the activity of the surface of the BN / BiOI material, and then designs the reaction parameters through an electrochemical deposition method to form a single-layer material.
[0033] Further, depositing a layer of BiOI particles on the surface of the single-layer material comprises:
[0034] 4) Take a mixture of BiOI particles in water with a mass fraction of 10-15%;
[0035] 5) With the ratio of single-layer material to BiOI particle mixture being 5 g: 2-3 ml, the BiOI particle mixture is first poured into the hopper of the spraying equipment, the spraying equipment is started, and then the single-layer material is sprayed. The spraying working pressure is 0.2-0.6 MPa, and the spraying distance between the single-layer material and the nozzle in the spraying equipment is 10-30 cm.
[0036] Description: The above method sprays BiOI particles on the surface of a single-layer material by spraying, so that the BiOI particles cover the outside of BN. The multi-level structure can improve the stability of the structure, the photocatalytic performance and the adsorption effect, thereby improving the efficiency of degradation.
[0037] Furthermore, the active agent is a surfactant.
[0038] Furthermore, the surfactant is a compound surfactant, and the preparation method of the compound surfactant is as follows:
[0039] Dissolve PEG in dichloromethane at a mass ratio of 1:1 to form a PEG solution; add N,N-dimethylaminopyridine accounting for 2-4% of the mass fraction of the PEG solution; cool in an ice bath, then dropwise add acetic anhydride accounting for 5% of the mass fraction of the PEG solution, and then stir in an ice bath for 12 hours to obtain a compound surfactant.
[0040] Description: The above surfactant combines the hydrophilicity of PEG and the silicon-philicity of silane coupling agent, and can effectively form a stable monomolecular film on the surface of BN particles, thereby improving the dispersibility and stability of BN in different media.
[0041] The beneficial effects of the present invention are:
[0042] The method of the present invention can improve the existing solvent thermal method to form a stable heterojunction. At the same time, the BN / BiOI material itself has photocatalytic properties, which can promote the formation of oxygen vacancies and e - / h + Separation can solve the problem that the wide band gap of BN limits its photocatalytic performance. The above method can solve the complicated operation of hydrophobic treatment for PFAS required by the existing method, and can improve the catalytic activity of BN / BiOI composite materials in PFAS. Specifically, in the BN / BiOI heterojunction, when irradiated with light, BiOI absorbs light energy to generate electron-hole pairs, and the electrons migrate to BN, while the holes remain in BiOI. Since the conduction band and valence band positions of BN and BiOI are different, this separation of electrons and holes can reduce their recombination probability, thereby improving the utilization rate of photogenerated charges. The Z-type heterojunction can also expand the light response range, allowing the material to utilize more light energy, thereby achieving low-cost and high-efficiency degradation, and the degradation of PFAS is diverse and the conditions are relatively mild. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a data diagram showing the results of degradation of PFOS in water by Example 1 of the present invention and Comparative Example 1;
[0044] Figure 2 This is a data diagram showing the results of degradation of PFOS in water by different addition amounts of BN / BiOI materials according to an embodiment of the present invention;
[0045] Figure 3 This is a data diagram of the degradation results of PFOS in water in Comparative Example 4;
[0046] Figure 4 It is a data diagram of the results of degradation of PFOS in water by Example 1 of the present invention and Comparative Example 3. DETAILED DESCRIPTION
[0047] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.
[0048] Embodiment 1: A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI, characterized by comprising:
[0049] S1. preparing BN / BiOI material;
[0050] S1-1, prepare solution A: dissolve 3 mmol (1.455 g) of Bi(NO3)3·5H2O and 4 mmol of BN in 20 mL of ethylene glycol, and stir for 30 min to form solution A; wherein the structure of BN is a nanotube structure, and the structure of Bi(NO3)3·5H2O is a nanosphere structure;
[0051] S1-2, preparing solution B: adding 3 mmol of KI to 10-30 mL of ethylene glycol, and mechanically stirring for 10 min at a mechanical stirring speed of 220 rpm to form solution B;
[0052] S1-3, adding solution A dropwise to solution B, stirring for 60 min, vacuum drying at 160° C. for 12 h, and then cooling to 23° C. to obtain a solid, and then washing the solid with distilled water and anhydrous ethanol in sequence, and then drying (at 60° C. for 24 h) to obtain a BN / BiOI material;
[0053] The dripping speed of adding solution A to solution B is 4 drops / s;
[0054] The stirring process is mechanical stirring at a speed of 220 rpm.
[0055] S2. Degrade PFAS in water;
[0056] The pH of the water to be degraded is adjusted to 3, and the BN / BiOI material is added to the water to be degraded to degrade until the PFAS concentration in the water to be degraded drops below the detection limit; wherein, the PFAS concentration in the water to be degraded is 50 mg / L, and the addition ratio of the BN / BiOI material to the water to be degraded is 75 mg:50 mL; the detection limit of the PFAS concentration is 1 mg / L.
[0057] Example 2: This example is different from Example 1 in that the raw material components for preparing the BN / BiOI material are different.
[0058] S1-1. Prepare solution A: dissolve 2 mmol of Bi(NO3)3·5H2O and 6.0 mmol of BN in 30 mL of ethylene glycol; S1-2. Prepare solution B: add 2 mmol of KI into 30 mL of ethylene glycol.
[0059] Example 3: This example is different from Example 1 in that the raw material components for preparing the BN / BiOI material are different.
[0060] S1-1. Prepare solution A: dissolve 4 mmol of Bi(NO3)3·5H2O and 1.5 mmol of BN in 10 mL of ethylene glycol; S1-2. Prepare solution B: add 4 mmol of KI into 10 mL of ethylene glycol.
[0061] Example 4: This example is different from Example 1 in that the amount of BN / BiOI material added to the water to be degraded is different, and the addition ratio of BN / BiOI material to the water to be degraded is 50 mg:50 mL.
[0062] Example 5: This example is different from Example 1 in that the amount of BN / BiOI material added to the water to be degraded is different, and the addition ratio of BN / BiOI material to the water to be degraded is 100 mg:50 mL.
[0063] Example 6: This example is different from Example 1 in that the stirring parameters are different: S1-1, stirring treatment for 25 minutes; S1-2, mechanical stirring for 5 minutes, and the mechanical stirring speed is 200 rpm; S1-3, stirring treatment for 55 minutes; the dropping speed of adding solution A to solution B is 3 drops / s; the above-mentioned stirring treatment is mechanical stirring, and the mechanical stirring speed is 200 rpm.
[0064] Example 7: This example is different from Example 1 in that the stirring parameters are different: S1-1, stirring treatment for 35 minutes; S1-2, mechanical stirring for 15 minutes, and the mechanical stirring speed is 230 rpm; S1-3, stirring treatment for 65 minutes; the dropping speed of adding solution A to solution B is 6 drops / s; the above-mentioned stirring treatment is mechanical stirring, and the mechanical stirring speed is 230 rpm.
[0065] Example 8: This example is different from Example 1 in that the parameters in the degradation method are different, and the pH of the water to be degraded is adjusted to 4.
[0066] Example 9: This example is different from Example 1 in that the parameters in the degradation method are different, and the pH of the water to be degraded is adjusted to 2.
[0067] Example 10: This example is different from Example 1 in that it provides another efficient degradation implementation method:
[0068] That is, the S2 degradation method is to add the BN / BiOI material to the water body to be degraded, first perform mechanical stirring for 2.5 minutes at 260 rpm, then perform dark adsorption under lightless conditions, and perform stirring during dark adsorption for 55 minutes; after the dark adsorption is completed, perform photocatalytic degradation under light conditions, and perform mechanical stirring during photocatalytic degradation at a speed of 160 rpm;
[0069] The stirring treatment is to stir continuously for 2.5 minutes at a stirring speed of 400 rpm, then stop stirring, turn on the ultrasonic treatment equipment, treat for 4 minutes at an ultrasonic frequency of 42 kHz, and then stir and treat simultaneously for 18 minutes; the ultrasonic mode of the ultrasonic treatment equipment is a pulse mode, and the pulse mode is to work for 5 seconds and rest for 5 seconds.
[0070] Example 11: The difference between this example and Example 10 is that the parameters of the stirring process are different. First, mechanical stirring is performed for 2 minutes at 280 rpm, and then dark adsorption is performed under lightless conditions. Stirring treatment is performed during the dark adsorption, and the dark adsorption time is 55 minutes. After the dark adsorption is completed, photocatalytic degradation is performed under light conditions. Mechanical stirring is performed during the photocatalytic degradation, and the mechanical stirring speed is 180 rpm. The stirring treatment is to continue stirring for 3 minutes at a stirring speed of 350 rpm, then stop stirring, turn on the ultrasonic treatment equipment, and treat for 3 minutes at an ultrasonic frequency of 40 kHz, and then stir and ultrasonicate for 15 minutes at the same time.
[0071] Example 12: The difference between this example and Example 10 is that the parameters of the stirring process are different. First, mechanical stirring is carried out for 3 minutes at 250rpm, and then dark adsorption is carried out under lightless conditions. Stirring treatment is carried out during the dark adsorption, and the dark adsorption time is 20 minutes; after the dark adsorption is completed, photocatalytic degradation is carried out under light conditions, and mechanical stirring is carried out during the photocatalytic degradation, and the mechanical stirring speed is 150rpm; the stirring treatment is to continue stirring for 2 minutes at a stirring speed of 500rpm, then stop stirring, turn on the ultrasonic treatment equipment, treat at an ultrasonic frequency of 45kHz, treat for 5 minutes, and then stir and ultrasonicate for 20 minutes at the same time.
[0072] Example 13: This example is different from Example 1 in that, in S1, after obtaining the BN / BiOI material, it is subjected to multi-level processing; the multi-level processing method is:
[0073] Using the BN / BiOI material obtained in S1 as the core particle, firstly deposit a layer of BN particles on the surface of the BN / BiOI material to obtain a single-layer material, and then deposit a layer of BiOI particles on the surface of the single-layer material to obtain a multi-layer BN / BiOI material;
[0074] The particle size of the BN / BiOI material is 50 nm, the particle size of the BN particles in the BN particle layer is 30 nm, and the particle size of the BiOI particles is 30 nm; in the multilayer BN / BiOI material, the thickness ratio of the BN / BiOI material, the BN particle layer, and the BiOI particles is 4:1.5:2.5;
[0075] Depositing a layer of BN particles on the surface of the BN / BiOI material comprises:
[0076] 1) Using an active agent at a ratio of 3 ml:15 g, the particles of the BN / BiOI material are surface modified and dried to obtain a pretreated BN / BiOI material;
[0077] 2) Take a mixture of 1.5% BN in boric acid; add zirconium oxide powder of the same mass as BN into the mixture;
[0078] 3) Add the pretreated BN / BiOI material to the BN-boric acid mixture at a ratio of 1 g:7 ml, apply a voltage of 48 V, and a current density of 13 mA / cm 2 , depositing for 28 minutes to obtain the single-layer material;
[0079] Depositing a BiOI particle layer on the surface of the single-layer material comprises:
[0080] 4) Take a mixture of BiOI particles in water with a mass fraction of 13%;
[0081] 5) With the ratio of single-layer material to BiOI particle mixture being 5 g:2.5 ml, the BiOI particle mixture is first poured into the hopper of the spraying equipment, the spraying equipment is started, and then the single-layer material is sprayed. The spraying working pressure is 0.5 MPa, and the spraying distance between the single-layer material and the nozzle in the spraying equipment is 20 cm.
[0082] Example 14: The difference between this example and Example 13 is that the parameters of the BN / BiOI material are different. The particle size of the BN / BiOI material is 115 nm, the particle size of the BN particles in the BN particle layer is 50 nm, and the particle size of the BiOI particles is 40 nm. In the multi-layer BN / BiOI material, the thickness ratio of the BN / BiOI material, the BN particle layer, and the BiOI particles is 4:2:2.
[0083] Example 15: The difference between this example and Example 13 is that the parameters of the BN / BiOI material are different. The particle size of the BN / BiOI material is 30 nm, the particle size of the BN particles in the BN particle layer is 20 nm, and the particle size of the BiOI particles is 20 nm. In the multi-layer BN / BiOI material, the thickness ratio of the BN / BiOI material, the BN particle layer, and the BiOI particles is 4:1:3.
[0084] Example 16: This example is different from Example 13 in that the parameters for depositing the BN particle layer and the BiOI particle layer are different. 1) The particles of the BN / BiOI material are surface modified with an active agent at a ratio of 1 ml:10 g and dried to obtain a pretreated BN / BiOI material;
[0085] 2) Take a mixture of 1% BN in boric acid;
[0086] 3) Add the pretreated BN / BiOI material to the BN boric acid mixture at a ratio of 1g:5ml, apply a voltage of 45V, and a current density of 10mA / cm 2 , depositing for 25 min to obtain the single-layer material;
[0087] 4) Take a mixture of BiOI particles in water with a mass fraction of 10%;
[0088] 5) With the ratio of single-layer material to BiOI particle mixture being 5 g:2 ml, the BiOI particle mixture is first poured into the hopper of the spraying equipment, the spraying equipment is started, and then the single-layer material is sprayed. The spraying working pressure is 0.2 MPa, and the spraying distance between the single-layer material and the nozzle in the spraying equipment is 10 cm.
[0089] Example 17: This example is different from Example 13 in that the parameters for depositing the BN particle layer and the BiOI particle layer are different. 1) The particles of the BN / BiOI material are surface modified with an active agent at a ratio of 5 ml:20 g and dried to obtain a pretreated BN / BiOI material;
[0090] 2) Take a mixture of 2% BN in boric acid;
[0091] 3) Add the pretreated BN / BiOI material to the BN boric acid mixture at a ratio of 1g:8ml, apply a voltage of 50V, and a current density of 15mA / cm 2 , depositing for 30 minutes to obtain the single-layer material;
[0092] 4) Take a mixture of BiOI particles in water with a mass fraction of 15%;
[0093] 5) With the ratio of single-layer material to BiOI particle mixture being 5 g:3 ml, the BiOI particle mixture is first poured into the hopper of the spraying equipment, the spraying equipment is started, and then the single-layer material is sprayed. The spraying working pressure is 0.6 MPa, and the spraying distance between the single-layer material and the nozzle in the spraying equipment is 30 cm.
[0094] Example 18: The difference between this example and Example 13 is that the surfactant is a compound surfactant, and the preparation method of the compound surfactant is as follows: dissolve PEG in dichloromethane at a mass ratio of 1:1 to form a PEG solution; add N,N-dimethylaminopyridine accounting for 3% of the mass fraction of the PEG solution; cool in an ice bath, and then add dropwise acetic anhydride accounting for 5% of the mass fraction of the PEG solution, and then stir in an ice bath for 12 hours to obtain the compound surfactant.
[0095] Example 19: This example is different from Example 18 in that the preparation parameters of the surfactant are different, and N,N-dimethylaminopyridine is added at a mass fraction of 4% of the PEG solution.
[0096] Example 20: This example is different from Example 18 in that the preparation parameters of the surfactant are different, and N,N-dimethylaminopyridine is added at a mass fraction of 2% of the PEG solution.
[0097] Example 21: This example is different from Example 1 in that the concentration of PFAS in the water to be degraded is 2 mg / L.
[0098] Example 22: This example is different from Example 1 in that the concentration of PFAS in the water to be degraded is 100 mg / L.
[0099] Experimental example:
[0100] The description of this experimental example is based on the scheme described in Example 1, and is intended to illustrate the practical application effect of the present invention.
[0101] Taking PFOS, a substance in PFAS, as an example, the degradation operations of Examples 1 to 20 above were carried out, and the results obtained were as follows:
[0102] 1. To explore the effects of different treatment methods on the degradation of PFOS in water;
[0103] Comparative Example 1: BiOI was used instead of BN / BiOI material to perform degradation in step S2 of Example 1;
[0104] Comparative Example 2: The BN / BiOI material of the prior art was obtained by the mechanical mixing method in the existing literature "Preparation and Performance Study of BiOI-based Composite Photocatalytic Materials", and the degradation of step S2 in Example 1 was carried out by using the BN / BiOI material of the prior art;
[0105] Comparative Example 3: The difference from Example 1 is that the pH value of the water to be degraded is not adjusted, and the pH values of the water to be degraded are 5, 7, 10, and 12 respectively;
[0106] Comparative Example 4: BN was used instead of BN / BiOI material to perform degradation in step S2 of Example 1. The results are as follows: Figure 3 As shown;
[0107] In summary, the degradation effects of Example 1, Example 10, Example 13 and Example 18, Comparative Example 1, Comparative Example 2 and Comparative Example 3 are compared;
[0108] 1 Prove the advantages of BN / BiOI materials for degradation:
[0109] Comparative Example 1 and Comparative Example 1, as Figure 1 As stated, Figure 1 The purple broken line of Example 1 has an obvious degradation effect. Compared with the green broken line of Comparative Example 1 and the black broken line without adding photocatalytic material, Example 1 can degrade PFOS to below the detection limit after 120 minutes, and the degradation is complete after 180 minutes. The degradation effect of Comparative Example 1 is quite different from that of Example 1, and almost no photocatalytic degradation is carried out, and the degradation effect is less than 15%. In addition, Figure 3 In the comparative example 4 shown, the efficiency of degradation using BN alone is very low. Therefore, it can be seen that the BN / BiOI material of Example 1 has a significant degradation effect.
[0110] 2 Prove the advantages of BN / BiOI material preparation method:
[0111] Comparing Example 1 with Comparative Example 2, in Comparative Example 2, when the degradation time is 120 min, the degradation rate is 48%, which is not degraded to half, and after 180 min, the degradation does not reach 50%. It can be seen that although the existing preparation method has a certain explanation effect, it is quite different from Example 1. Therefore, the BN / BiOI material preparation method in Example 1 is more preferred.
[0112] 3 Demonstrating the advantages of degradation method parameters:
[0113] Comparing the degradation effects of the water bodies to be degraded at various pH values in Example 1 and Comparative Example 3, Figure 4 As shown, Figure 4In the embodiment 1, except for the removal of 100% of PFOS at the initial solution pH of 3, PFOS was degraded to varying degrees when the pH range was 5 to 12, but the overall effect was reduced. Therefore, the setting of pH 3 in Example 1 is more preferred.
[0114] 4. Improved advantages of degradation methods:
[0115] Comparing Example 1 with Example 10, in Example 10, when the degradation time is 80 min, the degradation rate is 92%, while in Example 1, when the degradation time is 80 min, the degradation rate is 80%. It can be seen that the method in Example 10 accelerates the rate of the photocatalytic reaction and improves the degradation efficiency; this may be because the stirring method is consistent with the effect of adding the BN / BiOI material to the water to be degraded, thereby improving the overall catalytic efficiency.
[0116] Improved advantages of 5BN / BiOI materials:
[0117] Comparing Example 1 with Example 13, in Example 13, when the degradation time is 80 min, the degradation rate is 96%, while in Example 1, when the degradation time is 80 min, the degradation rate is 80%. It can be seen that the BN / BiOI material in Example 13 can further promote the photocatalytic reaction and improve the degradation efficiency; this may be because the shell layer can provide more reaction interfaces and light absorption areas, and the BN shell layer in the shell structure can confine the reactants, so that the reactants react inside the shell layer, thereby improving the selectivity and efficiency of the reaction.
[0118] 6. Improved advantages of active agents:
[0119] Comparing Example 13 with Example 18, in Example 18, when the degradation time is 75 min, the degradation rate is 95%. It can be seen that the use of the surfactant in Example 18 has a certain improvement effect. This may be because the surfactant can effectively form a stable monomolecular film on the surface of BN particles, thereby improving the dispersibility of BN in different media to improve the reaction efficiency.
[0120] Second, explore the effects of different parameters on the degradation of PFOS in water;
[0121] Compare Example 1, Example 2 with Example 3, and Example 6 with Example 7, as shown in Table 1;
[0122] Table 1 Effects of different parameters on the degradation of PFOS in water
[0123] parameter 60min degradation rate % 120min degradation rate % Example 1 52 95 Example 2 50 91 Example 3 45 93 Example 6 49 93 Example 7 50 92
[0124] 1. Optimize the amount of BN / BiOI material added:
[0125] Comparative Example 1, Example 4 and Example 5, as Figure 2 As shown, Figure 2 In Example 1, the addition amount of 75 mg has the best degradation effect. This may be because, at this addition amount, PFOS in water has a good contact effect with the BN / BiOI material and can promote the catalytic reaction. If it is less than 75 mg, such as 50 mg in Example 4, it may cause the problem of insufficient contact between PFOS in water and the BN / BiOI material. If it is greater than 75 mg, such as 100 mg in Example 5, it may hinder the continuation of the catalytic reaction and reduce the degradation process. Therefore, the BN / BiOI material addition amount parameter of Example 1 is more preferred.
[0126] 2 Optimize the raw material components for preparing BN / BiOI materials:
[0127] Comparing Example 1, Example 2 and Example 3, as shown in Table 1, the parameters of Example 1 are more preferred.
[0128] 3. Optimize mixing parameters:
[0129] By comparing Example 1, Example 6 and Example 7 in Table 1, it can be found that the stirring parameters of Example 1 are more preferred.
Claims
1. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI, characterized in that: include: S1. preparing BN / BiOI material; S1-1, preparing solution A: dissolving 2-4 mmol Bi(NO3)3·5H2O and 1.5-6.0 mmol BN in 10-30 mL ethylene glycol, stirring for 25-35 min to form solution A; wherein the structure of the BN is a nanotube structure, and the structure of the Bi(NO3)3·5H2O is a nanosphere structure; S1-2, preparing solution B: adding 2-4 mmol of KI to 10-30 mL of ethylene glycol, and mechanically stirring for 5-15 min at a mechanical stirring speed of 200-230 rpm to form solution B; S1-3, adding solution A dropwise to solution B, stirring for 55-65 min, vacuum drying at 155-165° C. for 10-14 h, and then cooling to 20-25° C. to obtain a solid, and then washing the solid with distilled water and anhydrous ethanol in sequence, and then drying to obtain a BN / BiOI material; S2. Degrade PFAS in water; The pH of the water to be degraded is adjusted to 2-4, and the BN / BiOI material is added to the water to be degraded to perform degradation until the PFAS concentration in the water to be degraded drops below the detection limit; wherein the PFAS concentration in the water to be degraded is 2-100 mg / L, and the addition ratio of the BN / BiOI material to the water to be degraded is 50-100 mg:50 ml.
2. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 1, characterized in that: In S2, the detection limit of the PFAS concentration is 1 mg / L.
3. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 1, characterized in that: In S2, after the BN / BiOI material is added to the water body to be degraded, it is first mechanically stirred for 2 to 3 minutes at 250 to 280 rpm, and then dark adsorption is carried out under lightless conditions. Stirring treatment is performed during the dark adsorption, and the dark adsorption time is 20 to 55 minutes. After the dark adsorption is completed, photocatalytic degradation is carried out under light conditions. Mechanical stirring is performed during the photocatalytic degradation, and the speed of mechanical stirring is 150 to 180 rpm.
4. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 1, characterized in that: The dripping speed of adding solution A to solution B is 3 to 6 drops / s.
5. The method for efficiently degrading PFAS using the Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 1, characterized in that: The stirring treatment is as follows: stirring continuously for 2 to 3 minutes at a stirring speed of 350 to 500 rpm, then stopping stirring, turning on ultrasonic treatment equipment, treating for 3 to 5 minutes at an ultrasonic frequency of 40 to 45 kHz, and then stirring and ultrasonic treatment for 15 to 20 minutes at the same time.
6. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 5, characterized in that: The ultrasonic mode of the ultrasonic processing device is a pulse mode, and the pulse mode works for 5 seconds and rests for 5 seconds.
7. The method for efficiently degrading PFAS using the Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 1, characterized in that: In S1, after obtaining the BN / BiOI material, it is subjected to multi-level processing; The multi-level processing method is: using the BN / BiOI material obtained in S1 as the core particle, firstly depositing a layer of BN particles on the surface of the BN / BiOI material to obtain a single-layer material, and then depositing a layer of BiOI particles on the surface of the single-layer material to obtain a multi-layer BN / BiOI material; The particle size of the BN / BiOI material is 30-115 nm, the particle size of the BN particles in the BN particle layer is 20-50 nm, and the particle size of the BiOI particles is 20-40 nm; in the multi-layer BN / BiOI material, the thickness ratio of the BN / BiOI material, the BN particle layer, and the BiOI particles is 4:1-2:2-3.
8. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 7, characterized in that: Depositing a layer of BN particles on the surface of the BN / BiOI material comprises: 1) Using an active agent at a ratio of 1-5 ml: 10-20 g to modify the surface of the BN / BiOI material particles and drying them to obtain a pretreated BN / BiOI material; 2) Take a mixture of 1-2% BN in boric acid; 3) Add the pretreated BN / BiOI material to the BN boric acid mixture at a ratio of 1g:5-8ml, apply a voltage of 45-50V, and a current density of 10-15mA / cm 2 , and deposit for 25 to 30 minutes to obtain the single-layer material.
9. A method for efficiently degrading PFAS using a Z-type heterojunction photocatalytic material BN / BiOI as claimed in claim 7, characterized in that: Depositing a BiOI particle layer on the surface of the single-layer material comprises: 4) Take a mixture of BiOI particles in water with a mass fraction of 10-15%; 5) With the ratio of single-layer material to BiOI particle mixture being 5 g: 2-3 ml, the BiOI particle mixture is first poured into the hopper of the spraying equipment, the spraying equipment is started, and then the single-layer material is sprayed. The spraying working pressure is 0.2-0.6 MPa, and the spraying distance between the single-layer material and the nozzle in the spraying equipment is 10-30 cm.